Analysis of the physicochemical parameters of the drilling of the Chocol-1 exploratory well located between the city of Comalcalco-Paraíso for the identification of a possible reservoir (Revista de Investigaciones Universidad del Quindío, 2022)
The search for hydrocarbons has forced to drill to greater depths, this requires the oil industry increasingly greater and difficult challenges to overcome, the present investigation was carried out with data provided from the Chocol-1 exploratory well located 8 km south of the city of Paraíso, as well as 10 km north of the city of Comalcalco.For the drilling of the Chocol-1 well, correlation was used, which has been considered one of the most applicable techniques in the oil industry, where first instance data is obtained by comparing certain parameters, for which data from the Pareto-1, Arrastradero-201 and Aarrastradero-301 wells. The use of the correlation methodology provides accurate data that allows extrapolation to field work, with significant savings in tools, equipment, personnel, and also a decrease in the number of exploratory wells, thus helping to minimize costs in various concepts.
Keywords: Correlation; oil; eras; deposit; physicochemical